Generating knowledge in a Learning Study – from the perspective of a teacher researcher. Issue 1 (1st January 2017) - Thorsten, Anja
Abstract: The purpose of this article is to discuss and describe how a clinical research method can be used to generate knowledge about teaching and learning. This will be addressed from a teacher researcher's perspective, taking a conducted Learning Study as the departure. Learning Study is an interventionist, iterative and collaborative research approach, focusing on the teaching of an object of learning. The actual study was conducted by a teacher researcher leading a teacher research team in a study about story-writing in primary school. The research process and the results are discussed using four areas that are described as dichotomies by Labaree (Labaree, D.F. 2003. "The Peculiar Problems of Preparing Educational Researchers." Educational Researcher 32 (4): 13–22). Labaree states that teacher researchers need to go from being normative, experimental, personal and particular to being analytical, theoretical, intellectual and universal . By using examples from the Learning Study, I argue that these areas do not have to be seen as dichotomies; instead they can be combined and intertwined. Thus, in a Learning Study, elements from both the teaching practice and the academic practice matter, thus enhancing the possibility that results are useful for practitioners.